Analisis Penguasaan Software Matlab Mahasiswa Pendidikan Matematika pada Materi Persamaan Linear dan Matriks - Andriyani, Iin; Rasyid, Muhammad Rusydi; Angriani, Andi Dian; Majid, Ahmad Farham; Baharuddin, (Alauddin Journal of Mathematics Education, 2022)
The purpose of this research is to find out how the level of mastery of students majoring in Mathematics Education in operating Matlab mathematics software on linear equations and matrices material. The type of research used is qualitative research. The type of research used is qualitative research. The source of this research data is students of the Department of Mathematics Education, UIN Alauddin Makassar in the class of 2016/2017. The data collection method used is a practical test and interview, with the data analysis technique Mod Mies and Huberman. Based on the results of data analysis, it was obtained that the steps that must be taken in operating the Matlab mathematics software application consist of: (1) understanding the problem by repeatedly reading the subject matter given and understanding what is being requested and finding solutions to problems by operating the matlab software. (2) make a settlement plan by finding the right concepts for the solution of the problem. (3) find a solution to the problem by referring to the concept used, then try to solve the obstacle if the program finds a problem or in other words error, then double-checks whether it is in accordance with its systematics. And after seeing the results that have been achieved mastery of mathematics software matlab students majoring in mathematics education for the 2016/2017 academic year are included in the capable category with a percentage of 75%.